Analysis of voltage and current at contact line power closure - Doleček, Radovan; Černý, Ondřej (Univerzita Pardubice, 2008)
The paper represents a part of research work on the field of elektromagnetic interference (EMI). Nowdays the railway techniques is very complicated and sophisticated both from viewpoint of railway infrastructure and from viewpoint of transport means. This research work was created on base of operating requirements. During work on contact line at AC 25 kV, 50 Hz for disconnection of contact line (i.e. track closure), it is necessary to connect this line with rail at the front and also at the end of protected work area by two earth rods. The paper deals with analysis of influence (i.e. coupling ways) of neighboring track contact line under these conditions which occur during the common operation or during fault current. The analysis is focused on the three circuit diagrams which arise out at section closure: isolated contact line, contact line one-sidedly connected with rail, contact line two-sidedly connected with rail. Generalize findings are mentioned in the conclusion of this paper. This work can be used as one part of background for research work on the field of traction system.
Napěťová a proudová analýza při výluce stopy trolejového vedení
Analyse der Spannung bei elektrischer Fahrleitungssperre